Angry or Weary? How Violence Impacts Attitudes toward Peace among Darfurian Refugees. (May 2020) - Hazlett, Chad
Does exposure to violence motivate individuals to support further violence or to seek peace? Such questions are central to our understanding of how conflicts evolve, terminate, and recur. Yet, convincing empirical evidence as to which response dominates—even in a specific case—has been elusive, owing to the inability to rule out confounding biases. This article employs a natural experiment based on the indiscriminacy of violence within villages in Darfur to examine how refugees' experiences of violence affect their attitudes toward peace. The results are consistent with a pro-peace or "weary" response: individuals directly harmed by violence were more likely to report that peace is possible and less likely to demand execution of their enemies. This provides microlevel evidence supporting earlier country-level work on "war-weariness" and extends the growing literature on the effects of violence on individuals by including attitudes toward peace as an important outcome. These findings suggest that victims harmed by violence during war can play a positive role in settlement and reconciliation processes.